산업부산물의 활성분체 및 세라믹섬유 혼입 콘크리트의 재료성능 평가 - 최승재(Seung Jai Choi); 양달훈(Dal Hun Yang); 이태희(Tae Hee Lee); 김장호(Jang Ho Jay Kim) (Ecology and Resilient Infrastructure, 2018)
Social infrastructures and industrial complexes have been actively constructed in South Korea since the 1960 s as part of the economic development plan, resulting in rapid industrialization. However, side-effects due to the industrialization have occurred. An increase in industrial by-products or wastes is a typical problem. Although some industrial by-products are recycled in Korea as well as worldwide, some wastes are landfilled or dumped in the sea. Although many researchers have executed various technologies for the disposal of industrial wastes, economic and environmental technologies have not been developed. Thus, this study aims to activate paper and fly ashes during the crush process to overcome the drawback of simple concrete mixed with paper and fly ashes, which cause a reduction in workability and strength, derive an optimal content and replacement ratio of concretes mixed with Energetically Modified Material (EMM), and evaluate the material performance. In addition, the basalt fiber is mixed simultaneously to achieve the reduction of cracks and improve the tensile strength. 한국은 1960년대부터 경제개발의 일환으로 사회기반시설, 공업단지 등이 활발히 건설되었으며 이로 인해 현재까지 산업화가 급격히 이루어졌다. 하지만 산업화에 따라 발생하는 산업부산물 또는 폐기물의 발생량이 점차 증가하고 있다. 일부 산업부산물은 재활용되고 있지만 대부분의 폐기물은 매립되는 실정이다. 이에 따라 산업폐기물 처리를 위한 다양한 방안이 검토되고 있으나 경제성과 환경성을 고려한 기술은 구축되어 있지 않다. 따라서 본 연구에서는 제지산업과 화력발전산업에서 발생하는 제지애시, 플라이애시를 활성화하여 적용한 활성분체와 세라믹섬유를 동시 혼입한 콘크리트의 재료성능을 검토하고자 한다. 애시를 분쇄과정에서 활성화시켜 수화도를 높여 물성을 향상시켰으며 동시에 콘크리트의 균열 저감을 위해 세라믹섬유를 동시 혼입하였다. 활성분체 및 세라믹섬유의 재료성능을 검증하기 위하여 KS 규격에 의거하여 원주형 콘크리트 공시체를 제작하였으며 슬럼프 및 재령 28일 압축강도를 측정하였다. 활성분체 플라이애시 20%, 제지애시 10% 혼입 콘크리트에서 활성분체 무혼입 콘크리트 압축강도의 90% 이상으로 나타난 것으로 확인하였다.